Textile finishing chemicals : an industrial guide - Flick, Ernest W. (Noyes Publications, 1990)
This book describes over 3,150 textile finishing chemicals available for industrial use. It has been compiled from information received from 74 manufacturers and distributors of these chemicals, including flame retardants, softeners, soil repellents, hand modifiers, antistatic agents, biocides, fixatives, scouring agents, dispersants, defoamers, anticracking agents, binders, stiffeners, and sequestering agents.